Vulnerabilidad social y adaptación comunitaria ante inundaciones en Cañaveral, Iquitos 2025 - Garcia Alvis, Piero Alexander (2025)
This quantitative, applied study, with a non-experimental, correlational, and cross sectional design, analyzed the relationship between social vulnerability and community adaptation strategies to flooding in the community of Cañaveral, Iquitos (2025). The population consisted of 31 homeowner-occupied households, using census sampling and a 25-item structured survey (α = 0.813). The descriptive analysis showed that social vulnerability is determined by economic and structural factors: low income, unstable employment, lack of basic services, and homes located in flood prone areas. The adaptive strategies identified are mostly reactive, with little prevention and weak community organization, further limited by the lack of state presence. The Shapiro-Wilk test justified the use of the Spearman test, finding a direct relationship between perceived vulnerability and adaptive actions. However, the effectiveness of these responses is low due to a lack of planning, coordination, and sustainable practices.